British Columbia : a new historical atlas - Hayes, Derek, 1947- (Douglas & McIntyre, 2012)
Features eye-opening maps, most previously unpublished, of gold seekers, surveyors, real estate promoters, diplomats, and more, alongside illuminating text that brings the province's history to life.